Answer:
8x^8/3 y^4 - The first option
Step-by-step explanation:
The first thing we need to do is the exponent outside the bracket and leave the 8 till last, because exponents always come before multiplying coefficients. When an term with an exponent is multiplied by another exponent outside a bracket, the exponents of both terms are multiplied by the exponent outside the bracket.
This means that the expression is now:
8(x^2*4/3 y^3*4/3)
First we can so the x term. The x term already has an exponent of 2, so the 2 is multiplied by the 4/3 exponent outside the bracket. 2*4/3 = 8/3, so the x term is now: x^8/3
The same happens to the y term: 3*4/3 simplifies to 4, so the y term is now y^4.
So now our expression is:
8(x^8/3 y^4)
Now the 8 outside the bracket simply multiplies on to the whole term so we finish with:
8x^8/3 y^4 - The first option.
Hope this helped!
Let the number of large bookcases be x and number of small bookcases be y, then
Maximise P = 80x + 50y;
subkect to:
6x + 2y ≤ 24
x, y ≥ 2
The corner points are (2, 2), (2, 6), (3.333, 2)
For (2, 2): P = 80(2) + 50(2) = 160 + 100 = 260
For (2, 6): P = 80(2) + 50(6) = 160 + 300 = 460
For (3.333, 2): P = 80(3.333) + 50(2) = 266.67 + 100 = 366.67
Therefore, for maximum profit, he should produce 2 large bookcases and 6 small bookcases.
Answer:
the system of equation has infinite solution
Step-by-step explanation:
,
Solve the first equation for x_2
Subtract 5x1 on both sides
Now substitute -5x1 on second equation
0=0
So the system of equation has infinite solution
9514 1404 393
Answer:
(√7)/3
Step-by-step explanation:
The relationship between tangent and cosine is ...
tan(α) = √(1/cos(α)² -1)
The cosine of the angle is given as 3/4, so the tangent is ...
tan(arccos(3/4)) = √(1/(3/4)² -1) = √(16/9 -1) = √(7/9)
tan(arccos(3/4)) = (√7)/3
Answer:
<u>f(x) = = (x + √2 i) (x - √2 i) (x - 2 ) (x + 1)</u>
Step-by-step explanation:
The given function is f(x) = x⁴ - x³ -2x -4
factor the polynomial function
f(x) = x⁴ - x³ -2x -4 = (x⁴ - 4) - (x³ + 2x ) ⇒ take (-) as a common from (- x³ -2x)
= (x² + 2 ) (x² - 2) - x (x² + 2) ⇒ take (x² + 2) as a common
= (x² + 2 ) ( x² - x - 2)
= (x + √2 i) (x - √2 i) (x -2 ) ( x+1)
Notes: (x⁴ - 4) = (x² + 2 ) (x² - 2)
(x² + 2)= (x + √2 i) (x - √2 i)
( x² - x - 2) = (x -2 ) ( x+1)